The Effect of Green Accounting and Tax Avoidance on Firm Value Moderated by the Board of Directors in Manufacturing Companies - Khalvin Aul Salcedo; Herlina Lusmeida (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
This study aims to examine the effect of green accounting and tax avoidance on firm value, with the board of directors as a moderating variable. The research uses a quantitative approach with panel data regression analysis based on 86 manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, totalling 430 firm-year observations. The results show that green accounting has a significant negative effect on firm value, indicating that environmental cost disclosures are not yet perceived positively by the market. Meanwhile, tax avoidance has a significant positive effect, reflecting its perception as an efficiency strategy by investors. Although the board of directors does not directly affect firm value, it significantly moderates the relationships between the independent variables and firm value: weakening the negative impact of green accounting and strengthening the positive impact of tax avoidance. These findings highlight the importance of corporate governance in managing environmental and fiscal strategies to optimize firm value.